PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIS, AUDITORI, VISUAL, INTELEKTUAL) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X MIA MAS MUALLIMIN UNIVA MEDAN - Asidah Hasibuan; Rofiqoh Hasan Harahap; Elia Putri; Juliandi Siregar (STKIP Subang, 2024)
This study aims to determine the effect of SAVI (Somatic, Auditory, Visual, Intellectual) learning model on students' physics learning outcomes. This type of research is quantitative with a quasi-experimental design on the subject matter of Effort and Energy. The population in this study were all X MIA class students by taking two classes as samples, namely X MIA-4 experimental class and X MIA-3 control class, random sampling technique. The experimental class received treatment using the SAVI learning model, while the control class used the Direct Instruction model. The learning outcomes test is 29 multiple choice questions with 5 different answer options that have been tested for validation and reliability first, then testing the hypothesis using the t-test. From the results of data analysis, the average score of the experimental class was 23.06 with a standard deviation of 3.83 while the control class was 18.41 with a standard deviation of 4.59. Based on the normality test obtained Lcount < Ltable = 0.151 < 0.159 and 0.155 < 0.156 the data is declared normally distributed. Homogeneity test ????count ≤ ????table = 0.720 < 1.828 states the sample is homogeneous. The t-test results tcount > ttable = 4.09 > 1.670 so that H1 is accepted. Based on these data that there is a significant effect of SAVI (Somatic, Auditory, Visual, Intellectual) learning model on student physics learning outcomes in class X MIA MAS Muallimin Univa Medan